IMPLEMENTATION OF CHLB IN PERSONAL HYGIENE TREATMENT AND SCABIES EXAMINATION AT NAHDATUL ULAMA ISLAMIC BOARDING SCHOOL SITI AISYAH MARTAPURA - mahdalena, mahdalena; Mahpolah, Mahpolah; Ilmi, Bahrul; Junaidi, Junaidi; Irfai, Irfai; Suroto, Suroto; Khair , Abdul; Barkinah , Tut; Dewi Dwiyanti , Ratih; Amperawati , Metty; Nurhamidi , Nurhamidi; Faturrahman, Faturrahman (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2022)
ABSTRACT Clean and Healthy Living Behavior (CHLB) is the main factor determining the health status of the pesantren community (boarding school leaders, ustadz/ustadzah, students, other employees at the pesantren). CHLB in Islamic boarding schools is a set of behaviors that are practiced on the base of awareness as a result of learning, which makes the pesantren community independently able to prevent disease, improve their health, and play an active role in creating a healthy environment. This community service activity expects female students to live clean and healthy behaviors, especially in personal hygiene care, dental and oral care and preventing scabies. The methods used are health services, education and health training. The results of community service activities through clinical symptom screening showed that 21 female students had clinical symptoms of scabies. Only a few Santriwati have a Clean and Healthy Lifestyle, because almost half of them still lack knowledge about personal hygiene. Many students have good dental and oral health care. For female students, to always maintain health and always carry out PHBS at all times, and immediately go to the health service for a health check if you experience clinical symptoms of scabies. Health workers should regularly, regularly provide health services and foster UKS in Islamic Boarding Schools, the health of the female students is always monitored.